Phylogenetic relationships between members of Amaranthaceae and Chenopodiaceae of lower gangetic plains using RAPD and ISSR markers (Bangladesh Journal of Botany, 2008)
The present study is the first report of phylogenetic relationships between some economically important members of Amaranthaceae and Chenopodiaceae of Lower Gangetic Plains of India, using RAPD and ISSR markers. A total of 293 RAPD and 177 ISSR fragments were generated with 15 (out of 50) decamer arbitrary primers and 11 (out of 30) microsatellite repeat anchored primers, respectively. Mean genetic similarities were estimated at 0.47 and 0.45 using RAPDs and ISSRs, respectively. The members of Chenopodiaceae are separated from those of Amaranthaceae in both the cases. The mantel test between the two Jaccard's similarity matrices gave r = 0.83, showing good correlation between RAPD and ISSR based similarities. However, in both the dendrograms Celosia sp. showed distant relationships with other amaranths. Key words: Amaranthaceae, Chenopodiaceae, RAPD, ISSR, Phylogenetic relationships Â  doi:10.3329/bjb.v36i1.1544 Bangladesh J. Bot. 36(1): 21-28, 2007 (June)